Factors affecting employees’ job performance in Telekom Malaysia, MITC, Melaka / Nurul Shazwannie Zainodin and Nur Hani Zalid - Zainodin, Nurul Shazwannie; Zalid, Nur Hani (2013)
Employees’ job performance is one of the famous issues aroused in many organizations nowadays. Organization should be able to retain and improve their employees’ job performance in order to gain competitive advantage. As for Telekom Malaysia, MITC, Melaka, researcher is interested to identify what are the predictors of employees’ job performance in this organization. This is because based on the observation made by researcher, TM Melaka have a good performance in terms of their sales performance, profit and revenue generated in the past few years. The first research objective is to determine the relationship between leadership and employees’ job performance. Second objective is to determine the relationship between training and employees’ job performance. The third objective is to determine the relationship between work knowledge and employees’ job performance. The fourth objective is to determine the most dominant factor that contributes towards employees’ job performance. The total number of respondents is 63 people selected from non-executives through Simple Random Sampling. The data were collected through distribution of questionnaire survey and interpreted into readable and informative data through Descriptive Analysis, Reliability Analysis, Pearson’s Correlation Analysis and Multiple Regressions Analysis. The findings supported all four objectives whereby there is a relationship between all three independent variables which are leadership, training and work knowledge with the dependent variable, employees’ job performance. The most dominant factor that contributes towards employees’ job performance is leadership.